Alterations of the Oral Microbiota Profiles in Chinese Patient With Oral Cancer - Li, Zixuan; Chen, Gang; Wang, Panpan; Sun, Minglei; Zhao, Junfang; Li, Ang; Sun, Qiang (Frontiers in Cellular and Infection Microbiology, 2021)
Oral cancer is the most common malignant tumor in oral and maxillofacial region, of which more than 90% are squamous cell carcinoma. The incidence of oral cancer is on the rise worldwide. The imbalance between the microorganism and its host may lead to the occurrence of oral malignant tumors.Accumulating evidence suggests that the oral microbiota plays an important role in oral cancer, yet the association between oral microbiota and oral cancer has not been studied comprehensively.In this study, metagenomic sequencing was used to compare the microbial composition of the three groups of samples from the oral cancer group, precancerous lesion group, and normal group.In terms of flora richness, we found that compared with oral cancer patients and healthy controls, the oral flora of patients with precancerous lesions is richer.In terms of flora diversity, there is little difference between the three groups of people.It was found that the three groups of samples had statistically significant differences in flora composition and metabolic function at the family, genus, and species level (P< 0.05). The significant differentially enriched flora in oral cancer samples is Bacteroidetes. At the genus level, the main differential enrichment is Prevotella, Peptostreptococcus, Carnobacterium, Dialistella, (P<0.05). At the species level, it was differentially enriched in Intermediate Prevotella and Oral Peptostreptococcus (p<0.05). The prediction of flora function shows that in oral cancer mainly include coenzyme A biosynthesis, phosphopantothenic acid biosynthesis, inosine 5'-phosphate degradation, riboflavin biosynthesis and so on.At the same time, it was found that the increase in C-reactive protein(CRP) in oral cancer patients is closely related to Prevotella intermedia.Overall, oral bacterial profiles showed significant difference between oral cancer group and normal group, which might be onsidered diagnostic markers and treatment targets. The data that support the findings of this study have been deposited into CNGB Sequence Archive (CNSA) of China National GeneBank DataBase (CNGBdb) with accession number CNP 0002274. http://db.cngb.org/cnsa/project/CNP0002274/reviewlink/